Beyond welcoming the strangers : integration policies and practices in Protestant Churches in Ireland and Italy - Passarelli, Alessia (Trinity College (Dublin, Ireland). Department of Sociology, 2015)
This thesis focuses on the integration approaches and strategies developed by Protestant Churches in Ireland and Italy following the arrival of an increasing number of migrants within their congregations. Ireland and Italy constitute interesting settings for my case studies for they share some similarities: first of all they share a similar narrative of becoming countries of immigration only recently, representing themselves as culturally homogenous before the arrival of migrants; secondly, Catholicism played an important role in shaping both Irishness and Italianness; thirdly, Protestant Churches constitute minority religious communities in both countries. As no previous sociological studies have focused on migrant integration projects in Protestant churches or on the juxtaposition of integration processes in Ireland and Italy, this study closes the knowledge gap in that regard.
Embargo End Date: 2022-01-01
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin, 2015